2009
DOI: 10.1111/j.1365-2133.2008.08981.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of bioavailability by lowering of fat content in topical formulations

Abstract: The rate of penetration of the active ingredients was inversely related to the lipid content, i.e. simple changes of the cosmetic properties by modifications of the lipid content may affect the efficacy of a formulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…This system has recently been evaluated in separate studies with regard to performance ), ability to visualize skin erythema ) and blanching (Zhai, 7/26 H. et al 2009) as well as in the assessment of the skin barrier function (Wiren, K. et al 2008). …”
Section: Tissue Viability Imager (Tivi)mentioning
confidence: 99%
“…This system has recently been evaluated in separate studies with regard to performance ), ability to visualize skin erythema ) and blanching (Zhai, 7/26 H. et al 2009) as well as in the assessment of the skin barrier function (Wiren, K. et al 2008). …”
Section: Tissue Viability Imager (Tivi)mentioning
confidence: 99%
“…The lipid content of a formulation can influence the thermodynamic activity of the active ingredient, resulting in a modified penetration profile [51] and penetration enhancers like oleic acid and ethanol changing the ceramide organization within the skin, and can reversibly reduce the barrier function of the stratum corneum [57] . Changes of lipid structure by Poloxamer 2.5% used for SLN stabilization have, however, been ruled out [58] , and intact SLNs 175 nm in size should not penetrate the skin [7] .…”
Section: Skin Uptake Studies: Creammentioning
confidence: 99%
“…The higher kinetic constants for SLN dispersions can be attributed to the lower viscosity of the outer aqueous phase [28] and to the increased thermodynamic activity of the GCs in the SLN dispersion due to the higher water content and therefore a decrease in the GC solubility in the formulation. Investigating volunteers Wirén et al [51] showed a higher activity of BMV (skin blanching) and benzyl nicotinate (erythema induction) by lowering the fat content in topi- ) were applied to a polyamide membrane (Higuchi plot). cal formulations which is attributed to a higher increase in drug concentration in the lower fat formulations with water evaporation when applied to the skin.…”
Section: Gc Release: Slnsmentioning
confidence: 99%
“…These features can be built in to a formulation without compromising its efficacy. For example, Wirén et al investigated the effect of changes in vehicle lipid content of o/w emulsions containing two active ingredients: benzyl nicotinate and β-methasone valerate on erythema and blanching of human skin in vivo [51]. Enhanced efficacy of both active ingredients (erythema with benzyl nicotinate and blanching with β-methasone valerate) was seen with the emulsions with the lowest (10%) lipid content, indicating that products can be designed with both efficacy and tactile acceptability in mind.…”
Section: Concentration Of the Components Of The Formulationmentioning
confidence: 99%